"The Effect Of Policy, Government Performance, And Information Technology On The Quality Of Financial Statements Of The Provincial Government Of Bangka Belitung Islands" - Devi Puspita Sari; Karmawan Karmawan; Julia Julia (Jurnal Indonesia Sosial Teknologi, 2023)
The purpose of this study is to determine how much variables affect the quality of financial statements contained in the report on the implementation of local government in the Bangka Belitung Islands Province. The variables that are the focus of this study are government policy, government performance, and the use of information technology as an independent variable, and the quality of financial statements as a dependent variable. To obtain data from these variables, 58 respondents were taken. In this study, primary data was obtained from the distribution of questionnaires to employees working in finance and budgeting who became a team in making local government budgeting reports in the Bangka Belitung Islands Province. As for the analysis method and hypothesis test using multiple regression test analysis. The results of hypothesis testing show that government policy variables have a negative and significant effect on the quality of financial statements. Meanwhile, government performance variables and the use of information technology have a positive and significant effect on the quality of financial statements. These three variables simultaneously affect the quality of financial statements. The value of the coefficient of determination shows that government policy, government performance, and the use of information technology have an influence on the quality of financial statements by 47,3 percent while 52,7 percent are influenced by other variables outside this study or other variables that are not included in this study. With this research, it is hoped that the government can make this research a reference in improving government performance in preparing quality and targeted financial statements. For further research, it is expected to explore other factors that can affect the quality of financial statements.